nowledge, Awareness and Practice of Breast Cancer Risk Factors and Breast Self-Examination with Clinical Examination and Fine Needle Aspiration of Suspicious Cases Among Educated Female in Tikrit City - Gheni, Nadia A. (International Journal of Psychosocial Rehabilitation, 2020)
Objective: to evaluate the knowledge, awareness and practice of breast cancer, risk factors, breast self- examination (BSE), and pick up of suspicious cases of breast masses with fine needle aspiration cytology among sample of educated population in Tikrit city/Iraq. Method: a cross-sectional, questionnaire-based study, a total of 335 participants were enrolled from the period of December 2018-March 2019 included 232 students, 69 schoolteachers, and 34 administrative staff, fine needle aspiration from 33 cases was performed. Results: 80.3% had heard about BSE (74.9%) were aware that’s BSE is the method for early detection of breast cancer. 74.8%% know that is breast cancer is the commonest among women in Iraq. Only 43.9% of the participants knew the procedure of BSE, 27.8% knew the best time to perform it, and only 88 (26.3%) of participant females practiced BSE. The answers about risk factors were more accurately achieved by the teachers. Social media and internet were the major source of knowledge about BSE, followed by doctors (30.7%)Fibrocystic disease of the breast was detected as the commonest type of breast masses aspirated (23 cases). Conclusion: satisfactory knowledge of educated female about breast cancer and breast self-examination, variable knowledge of various breast cancer risk factors along with inadequate practice of BSE as a method of early detection, serious need for medical health programs and actual activation of health care centers are very essential.